Studi Pencemaran E. coli Menggunakan Metode Petrifilm dan Lingkungan Mikrobiologis di Penampungan Air Tirto Lesti di Desa Poncokusumo : Study of E coli Pollution Using Petrifilm Methods and Microbiological Environment at Tirto Lesti Water Reservoir in Poncokusumo Village - Kholifah, Nur; Syauqi, Ahmad; Faisal (Jurnal SAINS ALAMI (Known Nature), 2025)
Residents use Tirto Lesti Shelter for their daily needs. Residents use the Tirto Lesti water source for cooking, washing, bathing, and also drinking. However, activities in the Lesti watershed and the lack of cleanliness at the Tirto Lesti water reservoir both affect the quality of the water and pollute it.  Water pollution can also cause disease, so testing is needed to determine the quality of the water in the reservoir.  The purpose of this study is to determine the source of Tirto Lesti water contaminated with E. coli bacteria and to obtain environmental values of microbiological parameters, including E. coli, as well as physical and chemical properties of the water, in order to assess the feasibility of water quality in the Tirto Lesti water reservoir. This study employs a quantitative descriptive method, utilising the Petrifilm method to calculate the research results. The results of the Biology parameters revealed a total of 210 cells per 100ml. In terms of Physical parameters, odourless, tasteless, turbidity 1,386 NTU, temperature 24.18°C, TDS 2.2488mg/L, chemical parameters pH 6,536mg/L, DO 5.04mg/L. According to the quality standards, biologically, it does not meet the requirements of PERMENKES RI No. 32 of 2017 Chapter 2. Meanwhile, in terms of physical and chemical parameters, it meets the requirements of PERMENKES RI No. 32 of 2017 Chapter 2. However, the measurement of DO does not meet the quality standards based on Government Regulation Number 22 of 2021, Class 1. Keywords: water, E coli, coliform, water pollution, water quality, storage tank ABSTRAK Penampungan Tirto Lesti dan digunakan oleh warga untuk kebutuhan sehari-hari. Warga menggunakan sumber air Tirto Lesti ini untuk memasak, mencuci, mandi, dan juga minum. Namun aktifitas di daerah aliran sungai Lesti dan kurangnya kebersihan di penampungan air Tirto Lesti mempengaruhi kualitas air dan mencemari air tersebut.  Pencemaran air juga dapat menyebabkan penyakit, jadi diperlukan pengujian untuk mengetahui kualitas air di penampungan.  Tujuan dari penelitian ini adalah untuk mengetahui  sumber air Tirto Lesti tercemar bakteri E. coli dan mendapatkan nilai lingkungan parameter mikrobiologis pada E. coli, fisika, kimia air dan dasar kelayakan kualitas air di penampungan air Tirto Lesti. Penelitian ini menggunakan metode deskriptif kuantitatif, menggunakan metode petrifilem dan menghitung hasil penelitian. Hasil parameter Biologi di temukan Total E. coli 210sel/100ml. Secara parameter Fisika tidak berbau, tidak berasa, kekeruhan 1.386 NTU, suhu 24.18°C, TDS 2.2488mg/L, Secara parameter kimia pH 6.536mg/L, DO 5.04mg/L. Menurut standar baku mutu secara Biologi tidak memenuhi persyaratan PERMENKES RI No 32 Tahun 2017 Bab 2. Sedangkan secara parameter fisika dan kimia masi memenuhi persyaratan PERMENKES RI No 32 Tahun 2017 Bab 2. Namun pengukuran DO tidak  memenuhi standar baku mutu berdasarkan PP Nomor 22 Tahun 2021 kelas 1. Kata kunci: air, E coli, coliform, pencemaran air, kualitas air, bak penampungan.